2018
DOI: 10.31832/smj.454249
|View full text |Cite
|
Sign up to set email alerts
|

Beyaz Yakalı Çalışanlarda İşe Bağlı Boyun, Sırt ve Omuz Bölgelerine Ait Kas İskelet Sistemi Rahatsızlıklarının ve İşe Devamsızlığza Etki Eden Faktörlerin İncelenmesi

Abstract: Amaç Bu çalışma ülkemizde beyaz yakalı çalışanlarda boyun, sırt ve omuz bölgesini içeren kas iskelet sistemi rahatsızlıklarının görülme oranını, ilişkili faktörleri ve işe devamsızlığa etki edebilecek faktörleri araştırmak amacıyla planlanmıştır. (Sakarya Tıp Dergisi 2018, 8(4):712-719) Gereç ve Yöntemler Olguların sosyo-demografi k bilgileri, tanısı konulan hastalıkları, telefon/bilgisayar kullanım süreleri, bilgisayar ile çalışma stilleri, çalışma ortamının ergonomik özellikleri ve vücut mekaniğine dair bilg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
2
0
3
Order By: Relevance
“…A research in Turkey found that 77.8% of participants did not engage in neck, back, or shoulder exercises during rest breaks. 21 In a study of individuals who work on a computer for over six hours a day, 35.9% did not engage in neck exercises. 22 A study conducted in Greece found that those who engaged in deep neck flexor muscle workouts had a reduction in levels of anxiety and despair.…”
Section: Discussionmentioning
confidence: 99%
“…A research in Turkey found that 77.8% of participants did not engage in neck, back, or shoulder exercises during rest breaks. 21 In a study of individuals who work on a computer for over six hours a day, 35.9% did not engage in neck exercises. 22 A study conducted in Greece found that those who engaged in deep neck flexor muscle workouts had a reduction in levels of anxiety and despair.…”
Section: Discussionmentioning
confidence: 99%
“…The present study reported higher prevalence in the lower back, neck, shoulder region, upper back, and wrist MSDs, and less in hips and ankles. Also, Akıncı et al and Kurnaz Ay et al found females have more loss of productivity and absence as they suffer from back, neck, and shoulder pain more as compared to females [22,23]. 80% of Indian undergraduates were suffering from MSDs symptoms in the head, neck, and eyes with 58 to 56 % in the dominant shoulder fingers, and hand during the online study (5).…”
Section: Discussionmentioning
confidence: 99%
“…Bu anketler kullanılarak, son yıllarda; üretim (yaygın olarak metal) (Gönen ve diğ., 2017;Singh, 2017;Boz Bayar, 2019;Özmehmet Tasan ve Felekoğlu, 2019;Yusof ve Shalahim, 2020;Kahya, 2020;Rathore, Pundir ve Iqbal, 2020;Hong, Lee ve Zhou, 2022), sağlık (Chanchai ve diğ., 2016;Wang ve diğ., 2017;Cheung, Szeto, Lai ve Ching, 2018;Ülgüdür ve Dedeli Caydam, 2020;Coskun Beyan, Dilek ve Demiral, 2020;Eyi ve Büyükakıncı, 2022), eğitim (Apaydın, Erol, Koçyiğit ve Elbasan, 2016;Kurt, İbiş, Aktuğ ve Aka, 2021;İde ve Gündüz, 2021), ofis (Özkan ve Kahya;Akıncı, Zenginler, Kara Kaya, Kurt ve Yeldan, 2018;Küçük, Düzenli Öztürk, Şenol, Özkeskin, 2018;Singh ve Singh, 2019;Alizadeh ve diğ., 2020;Ekin, Özçelik, ve Avşar Özcan, 2021;Kahya ve Erkaplan, 2022) gibi hizmet sektörlerinde çok sayıda ulusal ve uluslararası yayın bulunmaktadır. Otomotiv yardımcı sanayi işletmelerinde, işlemler esnasında, işin özelliğine bağlı olarak farklı fiziksel zorlanmalar yaşanmaktadır.…”
Section: Introductionunclassified